The relationship between learning styles and performance: a study on Generation Z accounting students / Azrinarizan Idarnis Abd Aziz, Tuan Zainun Tuan Mat and Mohd Ridzuan Hashim - Abd Aziz, Azrinarizan Idarnis; Tuan Mat, Tuan Zainun; Hashim, Mohd Ridzuan (Faculty of Accountancy, 2019)
Teaching and learning styles of students in higher learning institution is continuously become an important issue, especially facing with students in the new generation, i.e., generation Z (Gen Z), which also known as digital native. The educators face a challenge in order to ensure the institution is offering the most effective approach that suit with the generation Z behavior. Mismatch between the teaching and learning methods with the generation Z learning styles, may cause underperformance by the students. Higher education providers must ensure they provide students with current relevant courses that match with learning styles of the students, especially when designing the course assessment. In addition, the Malaysia government has made it compulsory for all higher educations to include soft skills in their formal and informal curriculum, and it must be part of the course assessment. This study is carried out to identify the preferred learning style of Gen Z accounting students and its relationship with the students’ performance. Literature shows that Gen Z is more individualistic than earlier generation (Gen X and Y), thus this study is investigating the preferred learning styles among them, either group or individual learning. Performance of the students is measured both based on the attainment of soft skill and academic performance (CGPA). This study also is examined the difference learning styles between Degree and Diploma accounting students in achieving their performance and soft skills. Data for this study is collected using survey questionnaire to randomly selected undergraduate accounting students in Klang Valley. Out of 300 questionnaires distributed to both degree and diploma accounting students, 211 were responded (105 degree students and 106 diploma students). To achieve the objectives of this study, data was analysed using the descriptive statistics, correlation analysis, and independent sample t-test. The results showed that degree students prefer group learning and diploma students prefer individual learning. The results also indicate that there is significant positive relationship between learning styles and attainment of students’ soft skills, but and no significant relationship with students’ academic performance. The findings in this study implicates that there is a need for the education provider to prepare the most suitable teaching and learning method for degree and diploma level to encourage the Generation Z students’ performance.